Characterization of eight species of anostomidae (Cypriniformes) fish on the basis of the nucleolar organizing region - Galetti, P. M.; Foresti, F. [UNESP]; Bertollo, L. A.C.; Moreira Fo, O. (Firenze University Press, 1984)
The present study shows the distribution of nucleolar organizing regions (NORs) in eight species of fresh-water fish of family Anostomidae belonging to the genera Leporinas, Leporellus and Schizodon, using silver staining techniques. Only two NORs per karyotype were encountered in all the species investigated. Despite the karyotypic similarity of these species, NORs appear in distinct chromosome and/or positions, thus representing excellent cytologic markers. © 1984 Taylor & Francis Group, LLC.